RESPON PERTUMBUHAN AWAL SETEK BATANG BUAH NAGA (Hylocereus costaricensis) TERHADAP ZPT HORMON TANAMAN UNGGUL (HANTU) DAN KOMPOSISI MEDIA TANAM - Rahmawati, Eka; Syahrani, Syahrani; Pujiono, Topan (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2019)
Effect of superior plant hormone ZPT (hantu) and composition of planting media on the initial growth of dragon fruit (Hylocereus costaricensis) stem cuttings.The research was began in November 2018 until February 2019, taking place in Sukodono Hamlet, Sumber Sari Village, Loa Kulu Subdistrict, Kutai Kartanegara Regency. This research was arranged in a Randomized Complete Block Design (RCBD) with 4 x 3 factorial analysis and repeated three times . The first factor is the provision of superior plant hormone ZPT (H) which consists of 4 levels, namely h0 (control or without treatment), h1 (1.5 ml L-1), h2 (3 ml L-1), and h3 (4,5 ml L-1) The second factor is the composition of the planting medium consisting of 3 levels, namely m1 (soil + cow manure (2: 1)), m2 (soil + cow manure (3: 1)), m3 (soil + cow manure (4: 1). The treatment of superior plant hormone ZPT administration had no significant effect on all parameters observed (first shoot time after planting, shoot length, number of shoots and stem circumference shoots 40, 60, and 80 days). The treatment of the composition of the planting medium has no significant effect on all parameters observed (first time shoots after planting, shoot length, number of shoots and stem circumference shoots 40, 60, and 80 days).